The legal nature of protecting the right to education in safe schools - Entdhar Saad Hamad / Hind Ali Muhammad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Education is a fundamental right in safe schools, as it represents the cornerstone of individual, societal, and successful development. Constitutional and legal legislation has affirmed the right to education and provided the necessary constitutional and legal protections in various constitutional and legal texts. However, recognizing the right to education in a safe school environment for students does not mean they are secure from government intervention or negligence, necessitating effective guarantees to ensure the practical implementation of this right by providing protection against any attack or negligence and addressing the factors affecting this right through the provision of basic requirements for students. Additionally, it is important to protect this right from any assault or harm to students or those responsible for the educational process by providing constitutional and legal protection .